Disappointed expectations and false hopes: The message of Ezekiel 13:1-16 in a time of change - Van Rooy, H. F. (HTS teologiese studies, 2002)
Ezekiel 13 forms part of a whole complex in the book of Ezekiel dealing with those prophetic voices challenged by the prophet Ezekiel. His audience paid no attention to his message and had expectations of a quick return from exile. These false expectations were bolstered by false prophets. The prophet unmasks their false-hood as part of an attempt to get the people to listen to his message aimed at repentance. This article explores the meaning of this crucial passage for contemporary South Africa.